2016
DOI: 10.1073/pnas.1607287113
|View full text |Cite
|
Sign up to set email alerts
|

Acid rain mitigation experiment shifts a forested watershed from a net sink to a net source of nitrogen

Abstract: Decades of acid rain have acidified forest soils and freshwaters throughout montane forests of the northeastern United States; the resulting loss of soil base cations is hypothesized to be responsible for limiting rates of forest growth throughout the region. In 1999, an experiment was conducted that reversed the long-term trend of soil base cation depletion and tested the hypothesis that calcium limits forest growth in acidified soils. Researchers added 1,189 kg Ca 2+ haas the pelletized mineral wollastonite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…The ongoing wollastonite addition experiment in New Hampshire has provided some of the most relevant and recent results on a possible link between Ca availability and watershed N release. This one‐time addition to a Ca‐depleted watershed had minimal effect on N release for about a decade, but over the ensuing 3 to 4 years, stream NO 3 − concentrations increased abruptly, shifting the watershed from an N sink to an N source (Rosi‐Marshall et al, ). Further work in this watershed indicated that release of N from soil to stream became more sensitive to hydrologic events during the period of high N release (Marinos et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ongoing wollastonite addition experiment in New Hampshire has provided some of the most relevant and recent results on a possible link between Ca availability and watershed N release. This one‐time addition to a Ca‐depleted watershed had minimal effect on N release for about a decade, but over the ensuing 3 to 4 years, stream NO 3 − concentrations increased abruptly, shifting the watershed from an N sink to an N source (Rosi‐Marshall et al, ). Further work in this watershed indicated that release of N from soil to stream became more sensitive to hydrologic events during the period of high N release (Marinos et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite these potential links between Ca and N availability, Ca‐N interactions remain poorly understood. For example, experimental addition of Ca in the form of wollastonite (CaSiO 3 ) to a Ca‐depleted watershed in New Hampshire, USA, resulted in increased forest growth (Battles et al, ) and decreases in microbial and inorganic N pools (Groffman et al, ) but also eventual increases in watershed export of N (Rosi‐Marshall et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In some regions, surface water nitrate concentrations have not responded strongly to declines in deposition (Garmo et al, 2014;Skjelkv ale et al, 2005), and nitrate leaching from N-saturated watersheds can increase even under constant N deposition (Curtis, Evans, Helliwell, & Monteith, 2005). Calcium additions to artificially induce acid rain recovery converted an experimental watershed from an N sink to source, suggesting future ecosystem responses to declines in atmospheric deposition may include N increases in surface waters (Rosi-Marshall, Bernhardt, Buso, Driscoll, & Likens, 2016). Additionally, N declines were observed in agricultural regions with extremely high TN concentrations (e.g., Iowa), where positive ammonium deposition trends have offset negative nitrate deposition trends (Li et al, 2016;Stoddard et al, 2003), and N deposition likely comprises a small fraction of the total N budget for each lake.…”
Section: Drivers Of Changementioning
confidence: 99%
“…Throughout the recent past, time‐series of data from small catchment ecosystems have provided key mechanistic insights into how hydrology and biogeochemistry interact to shape surface water chemistry, and thus how different landscapes may respond to natural and anthropogenic change . Given the suite of environmental pressures and challenges society currently faces, the termination of empirical data collection from field research infrastructures is troublesome, as the emergence of new conditions have historically had rapid and unforeseen consequences for catchment dynamics . A sample not collected is empirical data lost forever, which can be problematic as insights gleaned from the past may not necessarily be useful for predicting the future, especially if mechanistic understanding is lacking.…”
Section: Introductionmentioning
confidence: 99%